2022
DOI: 10.1021/acs.chemrestox.2c00064
|View full text |Cite
|
Sign up to set email alerts
|

Vaping Aerosols from Vitamin E Acetate and Tetrahydrocannabinol Oil: Chemistry and Composition

Abstract: The popularity of vaping cannabis products has increased sharply in recent years. In 2019, a sudden onset of electronic cigarette/vaping-associated lung injury (EVALI) was reported, leading to thousands of cases of lung illness and dozens of deaths due to the vaping of tetrahydrocannabinol (THC)-containing e-liquids that were obtained on the black market. A potential cause of EVALI has been hypothesized due to the illicit use of vitamin E acetate (VEA) in cannabis vape cartridges. However, the chemistry that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Instead, a wide range of degradation products commonly observed in vaping emissions could be seen in the resulting TIC (Figure B). Ultimately, analysis of these results found the presence of 4-methyl-1-pentanal (peak 1; t R = 9.805 min), 4-methyl-1-decene (peak 2; t R = 15.830 min), 3,7,11-trimethyl-1-dodecanol (peak 3; t R = 26.84 min), durohydroquinone (DHQ) (peak 4; t R = 27.103 min), 1-pristene (peak 5; t R = 28.073 min), and 2-hydroxy-4-methoxy-3,6-dimethyl benzaldehyde (peak 6; t R = 28.834 min), all of which have been previously detected in VEA vaping emissions. , ,, DQ was not observed at levels above the detection limit of the instrument, though DQ formation can be assumed due to the detection of 1-pristene and DHQ. , Ultimately, it is clear that the presence of O 2 when VEA is heated results in the production of compounds often found in VEA vaping emissions, indicating the importance of oxidation pathways during vaping thermal degradation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a wide range of degradation products commonly observed in vaping emissions could be seen in the resulting TIC (Figure B). Ultimately, analysis of these results found the presence of 4-methyl-1-pentanal (peak 1; t R = 9.805 min), 4-methyl-1-decene (peak 2; t R = 15.830 min), 3,7,11-trimethyl-1-dodecanol (peak 3; t R = 26.84 min), durohydroquinone (DHQ) (peak 4; t R = 27.103 min), 1-pristene (peak 5; t R = 28.073 min), and 2-hydroxy-4-methoxy-3,6-dimethyl benzaldehyde (peak 6; t R = 28.834 min), all of which have been previously detected in VEA vaping emissions. , ,, DQ was not observed at levels above the detection limit of the instrument, though DQ formation can be assumed due to the detection of 1-pristene and DHQ. , Ultimately, it is clear that the presence of O 2 when VEA is heated results in the production of compounds often found in VEA vaping emissions, indicating the importance of oxidation pathways during vaping thermal degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless, the presence and enhanced formation of OH radicals are noteworthy as a recent study by Li et al suggested that many degradation products of VEA may result from OH radical- and O 2 -mediated reactions. Radicals such as OH may initiate bond homolysis, dehydration, or H-abstraction on the side chain of VEA, followed by RO 2 radical-mediated chemistry to form highly oxygenated products observed in vaping emissions. , Such degradation pathways may occur simultaneously through pyrolysis-induced degradation, producing unique compounds that cannot be explained through pyrolysis alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that ketene is highly reactive and may be difficult to identify directly. Other respiratory irritants and known airway toxicants have also been identified with degradation of VEA, such as carbonyls, quinones, and other volatile products ( 120 123 ). In addition, VEA’s mode of action has been hypothesized to be a modification of pulmonary surfactant surface tension contributing to lung atelectasis, functioning as a linactant or line-activating molecule that binds to the boundary between lipid membranes, displacing endogenous surfactant.…”
Section: Potential Mechanisms Contributing To Evalimentioning
confidence: 99%
“…Major aerosol products in nicotine e-cigarettes may include formaldehyde, acrolein, acetaldehyde, and glycolaldehyde-releasing agents ( 149 ); for cannabinoid e-cigarettes, isoprene, methacrolein, methyl vinyl ketone, isoprene epoxide, butadiene, etc. are present ( 123 , 149 , 150 ). However, given the potential for cooccurrence of cigarette smoking among patients, care in selecting degradation product metabolites unique to the delivery mode is extremely important.…”
Section: Potential Mechanisms Contributing To Evalimentioning
confidence: 99%